1998
DOI: 10.1139/f98-094
|View full text |Cite
|
Sign up to set email alerts
|

Response of juvenile coho salmon (Oncorhynchus kisutch) and steelhead (Oncorhynchus mykiss) to the addition of salmon carcasses to two streams in southwestern Washington, U.S.A.

Abstract: Availability of organic matter and nutrients transported from the marine environment to streams by spawning salmon was increased in two small streams in southwestern Washington, U.S.A., by adding salmon carcasses from a nearby hatchery. Response of juvenile coho salmon (Oncorhynchus kisutch) and steelhead (Oncorhynchus mykiss) rearing at these sites was compared with nearby streams where few salmon spawned. Densities of age 0+ coho salmon and age 0+ and age 1+ steelhead increased following carcass additions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
213
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(225 citation statements)
references
References 27 publications
10
213
2
Order By: Relevance
“…Previous research has also found a positive effect of spawning salmon nutrients on juvenile salmonids, with the majority of studies utilizing experimental carcass additions. For example, carcass addition positively affected juvenile coho salmon body condition (Bilby et al 1998, juvenile coho salmon mass and body size (Wipfli et al 2003), juvenile coho salmon growth (Lang et al 2006, Giannico and Hinch 2007, and biomass of juvenile Atlantic salmon (Williams et al 2009). On the other hand, two studies did not find positive effects of carcass addition on juvenile cutthroat trout and steelhead: specific growth rate was less with carcasses than without (Wilzbach et al 2005) and growth did not change with carcass addition (Harvey and Wilzbach 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also found a positive effect of spawning salmon nutrients on juvenile salmonids, with the majority of studies utilizing experimental carcass additions. For example, carcass addition positively affected juvenile coho salmon body condition (Bilby et al 1998, juvenile coho salmon mass and body size (Wipfli et al 2003), juvenile coho salmon growth (Lang et al 2006, Giannico and Hinch 2007, and biomass of juvenile Atlantic salmon (Williams et al 2009). On the other hand, two studies did not find positive effects of carcass addition on juvenile cutthroat trout and steelhead: specific growth rate was less with carcasses than without (Wilzbach et al 2005) and growth did not change with carcass addition (Harvey and Wilzbach 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of spawning salmon increased energy intake of juvenile rainbow trout (Scheuerell et al 2007), and coho salmon (Heintz et al 2004, Armstrong et al 2010. Furthermore, nutrients from spawning salmon have been linked to improved condition and growth rate of juvenile coho in a number of carcass addition experiments (e.g., Bilby et al 1998. However, bioturbation during redd-digging could also reduce food availability through reduced invertebrate biomass .…”
Section: Introductionmentioning
confidence: 99%
“…However, contemporary evidence suggests that ecosystem structure alone does not necessarily reflect how it functions in supporting life. For example, field experiments in the US Pacific Northwest have shown that trophic manipulations (e.g., nutrient additions or salmon carcass introductions) that boost the abundance of potential prey organisms also boost subsequent fish growth (7)(8)(9)(10). In contrast, restoration of physical habitats by creating pools or adding structures yields ambiguous evidence that such efforts increase subsequent fish abundance and biomass (11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…This is typically accomplished by artificially adding salmon carcasses into the stream system during fall or winter (spawning) periods. The addition of MDN in this manner has been shown to have positive effects on the instream food web, salmonid juvenile survival, and on riparian forest health (Willson and Halpuka 1995;Bilby et al 1998;Naiman et al 2002;Schindler et al 2003;Wipfli et al 2003). Consideration should be given to the addition of salmon carcasses (MDN) into streams in the upper Grays River watershed.…”
Section: Riparian Corridor Restorationmentioning
confidence: 99%